1988
DOI: 10.1161/01.atv.8.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Ca++ antagonists and ACAT inhibitors promote cholesterol efflux from macrophages by different mechanisms. I. Characterization of cellular lipid metabolism.

Abstract: The effects of the slow C a + + channel blocker, nlfedlplne, and ACAT Inhibitor, octlmlbate, on the cholesterol metabolism of cholesterol-loaded macrophages were compared. We demonstrated that apollpoproteln A-) containing high density llpoprotelns (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(36 citation statements)
references
References 54 publications
0
34
0
Order By: Relevance
“…However, further detailed studies are necessary to clarify its mechanism. Recently, several investigators reported that ACAT inhibition inhibited foam cell formation (28) and prevented release into the circulation of apo B and VLDL-cholesterol at the liver both in vitro (7) and in vivo (8,9). Thus, besides dietary hypercholesterolemia, F-1394 may also have therapeutic potentials for the treatment of atherosclerosis as well as non-dietary hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 99%
“…However, further detailed studies are necessary to clarify its mechanism. Recently, several investigators reported that ACAT inhibition inhibited foam cell formation (28) and prevented release into the circulation of apo B and VLDL-cholesterol at the liver both in vitro (7) and in vivo (8,9). Thus, besides dietary hypercholesterolemia, F-1394 may also have therapeutic potentials for the treatment of atherosclerosis as well as non-dietary hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 99%
“…In adrenal cortex and ovary, ACAT' and neutral cholesteryl ester hydrolase regulate the intracellular storage pool of cholesterol for synthesis of steroidogenic hormones (31,(38)(39)(40)(41). ACAT activity has also been identified in placenta (33), lactating mammary gland (32), lung (19), aorta (5), macrophages (7,27,29,30), arterial smooth muscle cells (28,36), and fibroblasts of the lung (35) and skin (6,36). The physiologic role of ACAT in some of these tissues and cell types has not been clearly delineated. Cholesteryl esters can be a major form of tissue cholesterol in normal physiologic processes as well as pathologic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, in studies of mouse peritoneal macrophages, investigators have shown that the ACAT inhibitor octimibate, when present during foam cell formation, actually increased the uptake and degradation of acLDL and the accumulation of cholesterol in these cells. 8 ACAT inhibitors have also been studied in cultured primary human monocyte-derived macrophages (HMMs). HMMs can become lipid enriched when incubated with modified LDL 9 and have also been shown to release UC in the absence of added cholesterol acceptors in the medium.…”
mentioning
confidence: 99%